Indian oilseeds: present status and future needs - REDDY, P S; PATI, D (The Indian Journal of Agricultural Sciences, 2013)
With 21 % of world's area and 15% of world's production, India is one of the leading oilseeds producing countriesin the world. Also, oilseeds form the second largest agricultural commodities after cereals sharing 13% of the country's gross cropped area and accounts for nearly 5% of gross national product and 10% of the value of all agricultural products. The production and productivity of bulk of the oilseeds as wcll as the availability of vegetable oils in India are largely influenced by 9 annual oilseed crops, viz groundnut (Arachis hypogaea L.), rapeseed-mustard, sesame (Sesamum indicum L.), sunflower (Helianthus annuus.L), safflower (Carthamus tinctorius L.), soybean [Glycine max (L.) Merr.], niger [Guizotia abyssinica (L.f.) Cass.], castor (Ricinus communis L.) and linseed (linumÂ  usitatissimum. L.). There is a vast research infrastructure of oilseeds which includes the Directorate of Oilseeds Research.'the National Research Centres for Groundnut, Soybean and Rapeseed-Mustard besides a network of All-India Co-ordinated Research Project on Oilseeds centres located in the state agricultural universities. The establishment of Technology Mission on Oilseeds (TMO) has changed country's oil seeds scenario and brought near self-sufficiency in vegetable oils. There was a tremendous increase in the growth rates of area, production and productivity in each of the oilseed crops during the post-TMO periods. The productivity gains ,in each of the crops have come about primarily due to adoption of better technologies by the farmers. The latest technology, packages developed in each of the oilseed crops are given which include recently released varieties and recommendations under crop production and protection. The improved technology tested at thefarmers' fields under the project Frontline Demonstrations in Oilseed Crops showed the beneficial impact of improvedtechnologies over the farmers practices. The incremental benefit: cost ratio clearly showed that the technologies are cost effective. As such, substantial improvement in oilseeds production can be achieved even if the existing technologies are adopted partially by the oilseeds farmers.